Niby-fakty i niby-mity - Ciecierski, Tadeusz (Filozofia Nauki, 2009)
The paper is a reply to Leopold Hess' article "Proper Names - the Facts and the Myths". It is shown that the author misunderstood the issue of proper names and misconceived main ideas of the new theory of reference. The most important mistakes made by the author are: (i) considering the category of proper names in detachment from linguistic usage ;(ii) wrong reconstruction of the so-called modal argument and the notion of rigid designator; (iii) equivocating between two meanings of "a priori". All those mistakes are carefully analysed.